2016
DOI: 10.1017/s2045796016000287
|View full text |Cite
|
Sign up to set email alerts
|

Consumer-run services research and implications for mental health care

Abstract: Mental health consumers/survivors developed consumer-run services (CRSs) as alternatives to disempowering professionally run services that limited participant self-determination. The objective of the CRS is to promote recovery outcomes, not to cure or prevent mental illness. Recovery outcomes pave the way to a satisfying life as defined by the individual consumer despite repetitive episodes of disorder. Recovery is a way of life, which through empowerment, hope, self-efficacy, minimisation of self-stigma, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 29 publications
2
17
0
Order By: Relevance
“…[Author]'s role‐framework (2012) provided insight into participants' developing roles, relations, skills and self‐image. Our findings also support the statement that there is a relation between engagement with the relational environment and program management and (explicit) participant development (Author, 2015; Segal & Hayes, 2016).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…[Author]'s role‐framework (2012) provided insight into participants' developing roles, relations, skills and self‐image. Our findings also support the statement that there is a relation between engagement with the relational environment and program management and (explicit) participant development (Author, 2015; Segal & Hayes, 2016).…”
Section: Discussionsupporting
confidence: 87%
“…Self‐organised care is associated with participants' empowerment, specifically through the development of roles, relations, skills and self‐image (Brown, 2012). Participants who are less engaged with activities and program management, experience fewer benefits (Brown, 2012; Segal & Hayes, 2016). Peer support, in general, is associated with empowerment (Barker, Maguire, Bishop, & Stopa, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Participant responses suggested that allies have to work within practical constraints, seizing opportunities by corralling resources when they can, while at the same time advocating for the positions at multiple levels and across a range of settings. The stigma associated with mental illness further impacts on the perceived credibility of consumer researchers (Ghisoni et al., ; Hipes, Lucas, Phelan, & White, ; Segal & Hayes, ). Allies, on the other hand, are seen as credible due to their positions, professional background and research track record (Happell & Scholz, ; Hutchison, ).…”
Section: Discussionmentioning
confidence: 99%
“…; Scholz et al . ,b) or its conflation with other forms of involvement or more tokenistic practices (Segal & Hayes ; Scholz et al ., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Consumer leadership is difficult to define in part because of its inconsistency with traditional leadership styles. Consumer leadership has been described as less hierarchical in nature than conventional leadership models, in which power is concentrated at the top of hierarchies (Jones & Shattell ; Segal & Hayes ). Indeed, Piat et al .…”
Section: Introductionmentioning
confidence: 99%